PENGARUH NET PROFIT MARGIN (NPM), RETURN ON ASSET (ROA), DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM - Sri Intan Purnama; Intan Sari (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
This research is motivated by the importance of stock prices which is a factor that must be considered by investors in investing because stock prices show the performance of the issuer. This study aims to examine the effect of Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) both partially and simultaneously on stock prices in primary consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The data used in this study were obtained from secondary data in the form of annual financial report. The population in this study amounted to 105 companies and samples taken using purposive sampling techniquie were 34 companies. The analysis technique used is classical assumption test and hypothesis testing using SPSS v.20. The results of the analysis carried out show that partially Net Profit Margin (NPM) has no significant effect on stock prices, Return On Asset (ROA) has no significant effect on stock prices, Return On Equity (ROE) has a significant effect on stock prices. Meanwhile, simultaneously Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) has a significant effect on stock prices..